Tummy pain is not often what we think - Imaging findings in uncommon causes of abdominal pain in children and adolescents - A case series - Krishna Kiran Somashekar Karanth; Mahesh Mijar; Kishan B Shetty; Chetana S Sultanpuri (Wolters Kluwer Medknow Publications, 2023)
Acute abdominal pain is a common complaint in children. We came across several unusual causes of acute abdomen including jejunal haematoma, perforation and abdominal abscess following hydrostatic intussusception reduction, twisting of mesenteric cyst, perforation of sigmoid colon and Meckel's diverticulum presenting with intussusception. In this article, we aim to present imaging features of these entities so that paediatric surgeons, radiologists and other health-care providers are aware of these unusual manifestations of acute abdomen.